Marketing technology as a service : proven techniques that create value - Young, Laurie, 1955-; Burgess, Bev. (Chichester. UK. : John Wiley & Sons, 2010)
'Written by two marketers with long experience of these services, this book explores the developing expertise of leaders in this field. With an explorative and sometimes sceptical tone, it weaves sound academic research, developing concepts and fascinating case studies into a profound and challenging picture of a group of companies undergoing remarkable change. It demonstrates that the best are not only putting in place the essential basics of good service marketing; they are also developing organisational expertise and harnessing innovative, creative insight to offer attractive, profitable, and branded services to their customers. 'I really enjoyed the book From Products to Servicesby Mr Laurie Young. Encouraged by it, Haier accelerated its changeover from a traditional product-driven to a more customer-centric company. This new book Marketing Technology as a Service is another major contribution to technology companies for the cultivation of service needs worldwide.' Mr Zhang Ruimin, CEO and Chairman, Haier Group, Beijing 'Young and Burgess describe a shift in mindset and pragmatic techniques that are quite doable.' Rae Sedel, Managing Director, Global Technology Practice, Russell Reynolds Associates 'This book provides practical and insightful advice on how to use services to turn technology into value add solutions for real people.' Rudy Provoost, CEO, Philips Lighting 'Business leaders in India have been remarkably successful at offering technology based services like outsourcing across the world. Current $60 billion, India's outsourcing business is targeted to grow to $300 billion in the next ten years. In order to achieve these objectives, the Indian business community has to offer new value propositions and adapt to new trends that impact the outsourcing world, like cloud computing. Burgess and Young have put together the first comprehensive and practical guide for business leaders to meet their challenges of exponential growth.' Dr Mukesh Aghi, Chairman and CEO, Steria (India)'--
'The book will be divided into four sections. The proposed content of the book is as follows: An introduction to the technical services sector including an expos$1#OD(Bf the unique dynamics founded on technical networks, and why traditional marketing is not immediately relevant to technical service'--s
Includes bibliographical references and index.
Keywords: High technology industries -- Marketing